Perancangan Sistem Monitoring Energi Listrik Menggunakan NodeMCU ESP8266 dan PZEM-004T untuk Pengendalian Penggunaan Daya - Wira Ahmad; Dekki Widiatmoko; Fajar Kholid (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2024)
Electricity is one of the essential needs for society today, serving as a primary economicresource. The use of electricity in household sectors reached 50.80% in 2020,contributing to the total electricity consumption in Indonesia each month. To raiseawareness about excessive electricity usage leading to inflated electricity bills, there is aneed for a remote monitoring and control device, based on the Internet of Things (IoT),specifically targeting electronic appliances that consume electricity.Addressing this issue, a research study titled